Is the particle deposition in a cell exposure facility comparable to the lungs? A computer model approach. Issue 6 (2nd June 2020) - Karg, Erwin W.; Ferron, George A.; Bauer, Stefanie; Di Bucchianico, Sebastiano; Zimmermann, Ralf
Abstract: Cell exposure experiments at the air-liquid interface (ALI) are used increasingly as indicators for health effects and for the impact of aerosols on the lung. Thereby the aerosol particles are kept airborne and can deposit on a cell surface area similar to the human respiratory tract (RT). However, geometry and air flow rates of an ALI system deviate considerably from the RT. As the tissue-delivered particle dose to the lungs (TD) can hardly be measured, computer models of particle deposition are used here to mimic both the particle deposition at ALI and in the RT. An ALI exposure setup (VitroCell GmbH) for an airflow rate of 100 cm 3 min −1 is selected, where the particle deposition model has been verified experimentally. For the RT we use the hygroscopic lung deposition model of Ferron et al. (2013 ). Model runs are performed for the particle deposition and for the deposited particles per surface area in both the ALI and the RT. The results show that the ALI-deposited mass is 1-2 orders of magnitude higher than in the alveolar region, because the surface area of the lung region is substantially larger. A particle size range from 40 to 450 nm is identified, where the ratio of both the deposition in a lung region and the deposition at the ALI varies by a factor less than two. Mean values for this ratio are 31 and 101 for the tracheo-bronchial and the alveolar region, respectively. The same size range is found for the ratio of the deposited particles per surface area in a lung region and at the ALI. For this range the mean surface deposition at the ALI is 23- and 1575-times larger than in the tracheo-bronchial and the alveolar lung region, respectively. The effect is partly compensated by different flow rate and cell size. Copyright © 2020 American Association for Aerosol Research